Inaugurating 'Good Feeling between the United States and South Africa': The 1931 All-White Tour of South Africa. Issue 8 (15th July 2022) - Dyreson, Mark; Sikes, Michelle M.
ABSTRACT: In 1931, a track and field team sponsored by the American Amateur Athletic Union (AAU) toured South Africa, the first official visit of a US team to the African nation. The AAU fielded an all-white squad in this inaugural tour, even though African Americans held several world records in a variety of events during this era. Though it was not clear that US and South African officials explicitly coordinated to draw a colour line on the tour, it was clear that both sides were comfortable excluding non-whites. Nearly two decades later, when in 1950 the AAU selected another all-white team to visit South Africa, the African American press recalled the 1931 tour and condemned US officials for blatant racism. In 1931, however, both the black and white media were silent on the racial issues involved, in spite of an increasing focus on race and colour lines in athletics that developed in the era. Given the deeply embedded racial segregation systems in both South Africa and the US during this period, the first AAU visit to South Africa set a precedent that colour lines would be drawn and fought over in future track and field exchanges between the two nations.